Outlines of the geology of England and Wales with an introductory compendium of the general principles of that science, and comparative views of the structure of foreign countries - Conybeare, William Daniel 1787-1857 (Cambridge University Press, 2014)
In the early nineteenth century, the gifted stratigrapher and amateur geologist William Phillips (1773-1828) gave several lectures to interested young people in Tottenham on the subject of geology. These lectures were later collected into a book, which Phillips expanded in later versions. This reached its peak in 1822 when the clergyman William Daniel Conybeare (1787-1857) collaborated with Phillips to produce this rigorous and improved assessment of the geological composition of England and Wales. Although no second volume was ever published, the book had a tremendous impact on geologists throughout the United Kingdom and Europe, inspiring foreign scholars to produce equivalent volumes about their own countries. Conybeare's concern for the stratigraphy of fossils is especially remarkable for the time. William Fitton, later president of the Geological Society of London, praised the book highly, remarking that 'no equal portion of the earth's surface has ever been more ably illustrated'.